Risk determinants associated with the non-performance of periodic preventive exams for cervical cancer in the Northern Region, municipality of Porto de Moz, Pará - Brazil: a descriptive study - Ramos, Ad’villa Silva; Amorim, Murilo Tavares; Melo, Célio Amoêdo de; Arruda, José Eduardo Gomes; Carneiro, Alexandre Mansuê Ferreira (Revista JRG de Estudos Acadêmicos, 2024)
Quantitative descriptive cross-sectional study using a pre-coded questionnaire containing socioeconomic information of patients assisted at a Basic Health Unit in the municipality of Porto de Moz, located in the interior of the state of Pará, Brazil. The data was collected from October 10 to 28, 2022, with the participation of 263 women aged 18 to 64 years who sought care at the research site. The objective of this study was to identify factors related to non-adherence to the Papanicolaou test. Approximately 19.5% of the women did not undergo the exam due to being single, having at least one child, and being between the ages of 18 and 23. Among those who had incomplete elementary education, 29.4% did not take the test, and the majority earned less than one minimum wage. Furthermore, it was found that women in stable relationships did not feel the need to use condoms, which has negative implications for the public health network.